Is Research Reproducibility the New Data Management for Libraries? - Vitale, Cynthia R.H. (Bulletin of the Association for Information Science & Technology)
EDITOR'S SUMMARY With reproducibility of research becoming a leading issue in academia, libraries are examiningtheir role in promoting data and information transparency. The National Science Foundation's requirement for data management plans in research projects, grant applications stressing evidence of unbiased results and scholars' demands for standards for reproducibility together highlight the need for attention to the issue.Libraries increasingly seek staff with skills to support their data repositories, curation and data management services, and library and information science programs are responding to the growing need for specialization, including courses in research reproducibility. A ready solution may be for librarians to develop best practices for research transparency and methods to document research workflow. As the demand grows for evidence that research can be replicated, libraries are well positioned not only to manage research data properly but also to enable it to be analyzed for reproducibility.